2016
DOI: 10.18671/scifor.v44n110.19
|View full text |Cite
|
Sign up to set email alerts
|

Valores esperados para atributos de florestas ripárias em restauração em diferentes idades

Abstract: ResumoProjetos de restauração florestal vêm se multiplicando nos últimos anos no Brasil, mas ainda persiste a dificuldade em avaliar se o ecossistema, ao longo de sua trajetória temporal, está se desenvolvendo adequadamente ou se está aquém das expectativas. Neste estudo, visamos dar suporte ao monitoramento de matas ciliares em restauração em regiões de Floresta Estacional Semidecidual (Mata Atlântica), gerando valores esperados para diferentes atributos da comunidade arbórea em cada idade. Os valores de refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…the contemporary view of forest succession in which multiple trajectories are possible; Kauano et al 2013; Pereira et al 2013; Suganuma et al 2018), came the realization that successful restoration is not assured by the set of species planted. Studies have shown that the successful trajectory of restored forests is, to a certain extent, predictable in terms of structure, diversity, and ecosystem services (Liebsch et al 2008; Suganuma & Durigan 2015), but their composition is not predictable based on what was planted (Durigan et al 2016). However, restoration of the AF has frequently failed, due to biotic and abiotic constraints and also to poor maintenance during the first years of restoration, leading to alternative, stagnant, undesirable states (Sobanski & Marques 2014; Sansevero et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…the contemporary view of forest succession in which multiple trajectories are possible; Kauano et al 2013; Pereira et al 2013; Suganuma et al 2018), came the realization that successful restoration is not assured by the set of species planted. Studies have shown that the successful trajectory of restored forests is, to a certain extent, predictable in terms of structure, diversity, and ecosystem services (Liebsch et al 2008; Suganuma & Durigan 2015), but their composition is not predictable based on what was planted (Durigan et al 2016). However, restoration of the AF has frequently failed, due to biotic and abiotic constraints and also to poor maintenance during the first years of restoration, leading to alternative, stagnant, undesirable states (Sobanski & Marques 2014; Sansevero et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of suitable ecological indicators is a challenge for monitoring ecosystem quality. According to Durigan et al (2016) indicators should be easy to apply and, in the case of forest restoration, they should represent the gradual recovery of biodiversity, relevant ecological processes, and ecosystem services resulting of interventions.…”
Section: Management Improvements Through Monitoringmentioning
confidence: 99%
“…Therefore, the change from "forest monitoring" to "ecosystem monitoring" is a forest restoration requirement. The aim of a forest plantation is no longer an establishment of a production forest but a re-establishment of ecosystem processes (Albert et al, 2015;Bodini, 2012;Chaves et al, 2015;Durigan et al, 2016;Durigan and Ramos, 2013;Gatica-Saavedra et al, 2017;Reynolds et al, 2016;Whisenant, 1999).…”
Section: Requirements Of a Monitoring Conceptual Modelmentioning
confidence: 99%
See 2 more Smart Citations